Do the Current Accounting Regulations Facilitate the Creation of Provisions for Risks Related to IT Systems? - Białas, Małgorzata (Czy obecne regulacje w zakresie rachunkowości sprzyjają tworzeniu rezerw na ryzyka związane z systemami informatycznymi?, 2024)
Aim: The research objective of the study was to examine whether accounting regulations clearly and precisely define when and how provisions should be created for the effects of risk in the IT area. Moreover, it was considered whether Polish enterprises create such provisions, and if not, why not. Methodology: In connection with these research questions, an analysis of the applicable accounting regulations was carried out. Data from the Central Statistical Office were analyzed in terms of the level of provisions created. Additionally, the results of interviews with accountants were described. Finally, an analysis of the financial statements of two banks was conducted in terms of the value of provisions created for risks related to IT systems. Findings: The analysis of the data from the Central Statistical Office showed a very low level of provisions created by enterprises operating in Poland. As a result of the interviews with accountant, it turned out that the reason for the lack of creation of provisions is the difficulties associated with estimating the amount of such provisions and (relative) sense of security in this respect. Implications: According to the author, the research conducted and the interviews with accountants indicate the lack of appropriate regulations explaining the methods of creating provisions the effects of risk in the IT area. Education regarding the risks that IT systems may generate also seems to be crucial. Originality/value: Researchers mainly deal with general analysis of the level of provisions in enterprises. However, there is a lack of research in the literature on provisions for risk effects in the IT area. The conducted research indicates the desired directions of changes in the accounting regulation of the principles and methods of creating provisions.
Financial Sciences. Nauki o Finansach, 2024, vol. 29, no. 1, s. 65-73
Keywords: provisions; risk; IT systems; rezerwy; ryzyko; systemy IT